2022
DOI: 10.3390/jcdd9070228
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Index and Cardiovascular Disease among Middle-Aged and Older Chinese Adults: A Nationally Representative Cross-Sectional and Follow-Up Study

Abstract: Evidence for the association between the frailty index and cardiovascular disease (CVD) is inconclusive, and this association has not been evaluated in Chinese adults. We aim to examine the association between the frailty index and CVD among middle-aged and older Chinese adults. We conducted cross-sectional and cohort analyses using nationally representative data from the China Health and Retirement Longitudinal Study (CHARLS). From 2011 to 2018, 17,708 participants aged 45 years and older were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…However, the subgroup analysis revealed that the frailty index was the strongest predictor of stroke occurrence in the population aged 45-65 years. This finding is in line with previous studies [14,18], indicating that assessing frailty during midlife can aid in preventing the onset of stroke later in life.…”
Section: Discussionsupporting
confidence: 92%
“…However, the subgroup analysis revealed that the frailty index was the strongest predictor of stroke occurrence in the population aged 45-65 years. This finding is in line with previous studies [14,18], indicating that assessing frailty during midlife can aid in preventing the onset of stroke later in life.…”
Section: Discussionsupporting
confidence: 92%
“…In a meta-analysis conducted by Veronese et al [ 3 ], it was observed that both pre-frail (hazard ratio (HR) 2.80; CI 95% 1.83–4.28) and frail (HR 3.89; CI 95% 2.39–6.34) older adults had a higher risk for mortality by CVD compared to robust older adults. More recently, some studies have confirmed the association of pre-frailty and frailty phenotypes with increased risk of CVD [ 12 , 13 , 14 , 15 ] and of developing major adverse cardiovascular events [ 12 ]. A recent meta-analysis that included 185,229 middle-aged and older adults found a 2-fold increase in risk in the frail group and 1.5-fold in the pre-frail group for mortality from CVD and cancer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Atkins et al reported that sarcopenia might be associated with cardiovascular mortality ( 42 ). Another long-term follow-up study of 15,000 Chinese middle-aged and elderly people showed that compared with normal people, the incidence of cardiovascular disease in middle-aged and elderly people with sarcopenia increased by 72%, and the risk of cardiovascular events increased by 33% ( 43 ). Consistently, the present study indicated that sarcopenia was an independent risk factor for all-cause mortality in patients with DFUs.…”
Section: Discussionmentioning
confidence: 99%